Heterometallic Actinide‐Containing Photoresponsive Metal‐Organic Frameworks: Dynamic and Static Tuning of Electronic Properties. (24th February 2021) - Martin, Corey R.; Leith, Gabrielle A.; Kittikhunnatham, Preecha; Park, Kyoung Chul; Ejegbavwo, Otega A.; Mathur, Abhijai; Callahan, Cameron R.; Desmond, Shelby L.; Keener, Myles R.; Ahmed, Fiaz; Pandey, Shubham; Smith, Mark D.; et al.
Abstract: Acquiring fundamental knowledge of properties of actinide‐based materials is a necessary step to create new possibilities for addressing the current challenges in the nuclear energy and nuclear waste sectors. In this report, we established a photophysics–electronics correlation for actinide‐containing metal‐organic frameworks (An‐MOFs) as a function of excitation wavelength, for the first time. A stepwise approach for dynamically modulating electronic properties was applied for the first time towards actinide‐based heterometallic MOFs through integration of photochromic linkers. Optical cycling, modeling of density of states near the Fermi edge, conductivity measurements, and photoisomerization kinetics were employed to shed light on the process of tailoring optoelectronic properties of An‐MOFs. Furthermore, the first photochromic MOF‐based field‐effect transistor, in which the field‐effect response could be changed through light exposure, was constructed. As a demonstration, the change in current upon light exposure was sufficient to operate a two‐LED fail‐safe indicator circuit. Abstract : The merging of heterometallic actinide‐containing metal‐organic frameworks and photochromic moieties allowed for dynamic tailoring of electronics properties as a function of excitation wavelength. Visualization of material photoswitchable behavior was demonstrated by construction of the first photochromic MOF‐based field‐effect transistor.